2013
DOI: 10.1021/ef401887r
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamic Simulations of a Pilot-Scale Transport Coal Gasifier: Evaluation of Reaction Kinetics

Abstract: The U.S. Department of Energy’s National Energy Technology Laboratory has developed a software platform titled Carbonaceous Chemistry for Computational Modeling (C3M) that can be used to seamlessly connect the reaction kinetics typically found in the gasification process to various computational fluid dynamic (CFD) packages, including MFIX, ANSYS-FLUENT, and BARRACUDA, for advanced gasifier simulation. In this study, a pilot-scale transport gasifier was simulated by employing the C3M platform to incorporate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The char–steam gasification rate from MGAS model (A = 2.25 × 10 3 atm −1 s −1 ) is used; however, the predicted mole fraction of CO and H 2 out of the riser is lower than the experimental data. Similarly, Li et al and Guenther et al also found that MGAS model underestimated the mole fraction of CO and H 2 in the simulations of gasification processes of Kellogg Brown & Root, Inc. (KBR) gasifier, because of the low steam gasification rate in MGAS model . The char–steam reaction rate is dependent on coal type.…”
Section: Resultsmentioning
confidence: 93%
“…The char–steam gasification rate from MGAS model (A = 2.25 × 10 3 atm −1 s −1 ) is used; however, the predicted mole fraction of CO and H 2 out of the riser is lower than the experimental data. Similarly, Li et al and Guenther et al also found that MGAS model underestimated the mole fraction of CO and H 2 in the simulations of gasification processes of Kellogg Brown & Root, Inc. (KBR) gasifier, because of the low steam gasification rate in MGAS model . The char–steam reaction rate is dependent on coal type.…”
Section: Resultsmentioning
confidence: 93%
“…The CPD model includes rates for bridge breaking and side chain release, percolation lattice statistics to relate the number of broken bridges to the distribution of clusters that detach from the lattice, vapor-liquid equilibrium to determine the sizes of detached clusters that vaporize to form tar, and crosslinking of non-vaporized detached fragments that become part of the char. The CPD model has been shown to agree with pyrolysis data for a wide range of coals, heating rates, temperatures, and pressures, [3,12, and hence is used as an example reference model in this paper.…”
Section: Cpd Modelmentioning
confidence: 99%
“…Niksa [10,11] developed a method for a given heating rate to determine coefficients for a 1-step devolatilization model from PC Coal Lab using his Flashchain network model and other similar char chemistry models. Li et al [12] also developed a package to interface with computational fluid dynamics software to develop coefficients for a 1-step devolatilization model based on several different network models for coal combustion, called Carbonaceous Chemistry for Computational Modeling, nicknamed C3M . Hashimoto et al [13] used an iterative technique to generate coal devolatilization rate parameters for a CFD model, taking the particle temperature history from each previous CFD particle trajectory to determine rate parameters for the next iteration.…”
Section: Introductionmentioning
confidence: 99%
“…Following this validation hierarchy, a series of validation experiments and corresponding simulation runs have been performed. The CFD simulations are based on an open-source multiphase flow computer code MFIX (https://mfix.netl.doe.gov), which has been validated successfully for multiphase flow simulations including those with chemical reactions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%